Large keratocystic odontogenic tumor of the mandible - Sri Krishna Koppula; Ashutosh Kumar; Devarshi Nandi; Anand Choudhary (Wolters Kluwer Medknow Publications, 2015)
The odontogenic keratocyst (OKC) is a rare odontogenic cyst of epithelial origin. There are many types of cysts of the jaws, but what make the odontogenic keratocyst unusual are its characteristic features including its potentially aggressive behavior, high recurrence rate, and an association with the nevoid basal cell carcinoma syndrome. Odontogenic keratocysts, now reclassified as keratocystic odontogenic tumors (KCOTs) by the World Health Organization, are a clinical entity with a characteristic microscopic picture, kinetic growth, and biological behavior. The characteristic features are unique among all the different inflammatory and developmental cysts that occur in the jaws. In this report, we present a 35-year-old female patient with a massive KCOT with buccal cortical plate expansion and unusual anteroposterior extension extending from the premolar area up to the condyle.